2019
DOI: 10.1155/2019/9581259
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Metastasis in a Patient with Head and Neck Cancer: A Case Report and Review of the Literature

Abstract: Cardiac metastasis from a primary head and neck cancer is a rare finding. Most patients with cardiac metastases have nonspecific symptoms that may vary depending on the severity and location of the lesion. Due to the infrequency of reported cases, there are no clear guidelines for the diagnosis or management of cardiac metastasis in head and neck cancer patients. In this report, we discuss the case of a patient with a primary diagnosis of oral tongue cancer who developed a cardiac metastasis that was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…[ 7 ] In a literature review of cardiac metastasis of head and neck cancer detected ante-mortem, Kim et al reported 23 cases of which 12 were tumors of the tongue thus representing a large majority with 52%. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] In a literature review of cardiac metastasis of head and neck cancer detected ante-mortem, Kim et al reported 23 cases of which 12 were tumors of the tongue thus representing a large majority with 52%. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…In patients with lymphoma, the cardiac involvement is seen in 8–15% of the cases and most of them are of B cell origin [ 34 ]. Clinical manifestations are highly variable, including heart failure, arrhythmias, valvular disease, and cardiac tamponade [ 35 ]. Due to the varying clinical presentations of cardiac lymphoma metastases, the detection is often incidental.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with lymphoma the cardiac involvement is seen in 8-15% of the cases and most of them are of B cell origin [25]. Clinical manifestations are highly variable, including heart failure, arrhythmias, valvular disease, and cardiac tamponade [26]. Due to the varying clinical presentations of cardiac lymphoma metastases the detection is often incidental.…”
Section: Discussionmentioning
confidence: 99%